2016
DOI: 10.1186/s13071-016-1300-4
|View full text |Cite
|
Sign up to set email alerts
|

Description of Sergentomyia phadangensis n. sp. (Diptera, Psychodidae) of Thailand

Abstract: BackgroundSince 1996, there are emerging autochthonous cases of leishmaniasis in Thailand due to Leishmania “siamensis” and to L. martiniquensis explaining a recent interest for the sand fly fauna where Sergentomyia gemmea and Se. barraudi have been considered possible vectors in the country.MethodsField studies were undertaken in a cave of Phitsanulok Province, Thailand. Phlebotomine sandflies have been studied morphologically and some have been processed for molecular biology (sequencing of cytB rDNA).Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…[37][38][39][40][41][42][43][44][45][46][47] A recent review of sandfly distribution in Thailand indicated that at least 27 species of the four genera, Sergentomyia, Phlebotomus, Idiophlebotomus, and Chinius were identified. 42,43 Certain species such as Sergentomyia gemmea are the most predominant species in the north 33 as well as in the south. 24,42,44 The prevalence of S. gemmea was as high as 85-95% in the northern and southern areas.…”
Section: Sandfly Distribution and Potential Vectormentioning
confidence: 99%
“…[37][38][39][40][41][42][43][44][45][46][47] A recent review of sandfly distribution in Thailand indicated that at least 27 species of the four genera, Sergentomyia, Phlebotomus, Idiophlebotomus, and Chinius were identified. 42,43 Certain species such as Sergentomyia gemmea are the most predominant species in the north 33 as well as in the south. 24,42,44 The prevalence of S. gemmea was as high as 85-95% in the northern and southern areas.…”
Section: Sandfly Distribution and Potential Vectormentioning
confidence: 99%
“…In the present study, DNA barcoding analysis was performed to identify the species of the 24 female sand fly specimens that could be classified only to the genus level based on morphological characters; 12 of these 24 specimens were subsequently identified using DNA barcoding to the species level, including P. mascomai , S. bailyi , S. gemmea , S. perturbans and S. rudnicki ; however, the remaining 12 specimens were still identified to the genus level only. These unclassified species may be newly recorded species; however, an analysis using additional DNA markers, such as the Cytb gene [ 16 , 44 ], is warranted prior to reaching a definitive conclusion. The DNA barcoding showed that five (11.4%) of the 44 specimens identified to species level on the basis of morphological chararacters actually belonged to a different species.…”
Section: Discussionmentioning
confidence: 99%
“…Although Thailand is not considered to be an endemic country for leishmaniasis, since 1999 there has been an increase in the number of reported cases of autochthonous leishmaniasis in several regions of the country [ 15 ]. A recent review of sand fly distribution in Thailand indicated that at least 27 species of the genera Sergentomyia , Phlebotomus , Idiophlebotomus and Chinius have been identified [ 16 , 17 ]. Sergentomyia gemmea is the predominant species in Thailand and is considered to be a potential vector of L. orientalis [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Identi cation of the specimens were done by using Adler and eodor (1926), Raynal (1937Raynal ( ), eodor (1948, Kirk and Lewis (1951), Quate (1962), Lewis (1973Lewis ( , 1978, Leng (1997). Terminology and abbreviations follows Quate (1962) except antennal formulas and thorax, which follows Polseela et al (2016) and Galati et al (2017) respectively. e specimens were studied using BX51 and CH-2 microscopes (Olympus Co., Japan) and measured using the microscopy imaging so ware cellSens standard (Olympus Co., Japan).…”
Section: Specimen Preservation Preparation and Identi Cationmentioning
confidence: 99%